Contro i “taxi del mare”. La contronarrazione delle ONG e il caso SeaWatch3 - Sampugnaro, Rossana (SocietàMutamentoPolitica, 2020)
With the end of Mare Nostrum, the outsourcing of rescue operations and the attempt to europeanise the crisis, the role of NGOs in the SAR area is shifting from a complementary to a fundamental one in rescue operations as a whole. The rapid change in the regulatory framework governing Italian and European actions requires a constant redefinition of their roles and action strategies in the SAR area. A consequence (unforeseen) of their presence has been the criminalization of their activities, which are considered functional with regard to human trackers. The rhetoric of “sea taxis” has produced a change in NGO communication strategy, with a more careful description of their actions to save migrants. The structures of communication have become more complex and professionalized, while a shrewder use is made of social networks in a hybrid system. The SeaWatch3 and Carola Rackete case study is an example of this change in strategy, which involves major personalization of communication, with extended use of the personal stories of migrants, crew and supporters. The case study is conducted with a qualitative methodology that takes into account the press review of 17 national newspapers, self-produced images by NGOs, and the collection of tweets (with NODEXL) during the long phases of the crisis. From the twittersphere emerges a) the progressive internationalization of the case, with the intervention of the main European media, the main political actors, the NGO network, and b) the attempts of reframing promoted especially by NGOs.